Farmers' Bussiness as Usual Increase Lead (Pb) Level in the Soil: a Case Study Horticulture Land in Batu, Indonesia - Reni Ustiatik; Beauty Laras Setia Pertiwi; R. M. Yusuf Adi Pujo Nugroho; Georona Kusma Albarki; Siti Nur â€˜Azizah; Ayu Putri Ariska; Yulia Nuraini; Syahrul Kurniawan (Jurnal Penelitian Pendidikan IPA, 2024)
Lead (Pb) is a toxic heavy metal for humans. Agrochemical applications contribute to Pb contamination and accumulation in plants which is harmful to humans. This study aims to investigate the habits of horticultural farmers in applying inorganic fertilizers and pesticides intensively on Pb concentration in the soil and cultivated plants, and its effect on plant growth. The measured parameters consisted of soil and plant Pb content, soil pH, organic C, total N, available P, and exchangeable K. This study used a randomized block design consisting of 4 treatments (Control (KT); (PR); (TN); and (TP)). The results showed that horticultural farmers' dosage of inorganic fertilizers exceeded Indonesia Ministry of Agriculture recommendation. The application of inorganic fertilizers and pesticides by farmers (business as usual) increased Pb content in plants up to 31.46 mg/kg. Besides the application of inorganic fertilizers increases fertilizer residues in the soil by up to 65%, which increases environmental pollution even though the application of inorganic fertilizers increases plant growth and production (shoot length,Â  the number of leaves, and plant dry weight). Thus, wisely applying agrochemicals is required in order to support plant growth and production without further environmental problems.